Analisis Kedudukan Kepala Pemerintahan Ibu Kota Nusantara dalam Undang-Undang Nomor 3 Tahun 2022 Berdasarkan Sistem Pemerintahan Daerah - Jordan Petra Jeremi Situmorang; Tito Jeremia Sanggaam Marisi Situmorang; Laurentius Marcell (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
Currently, the issuance of Law Number 3 of 2022 concerning the National Capital is a concrete step taken by the Government to seek the relocation and development of a new National Capital, because economic growth has so far been considered too Java-centric by some in the community. However, it cannot be denied that after the issuance of this law it triggered new problems, including the problem regarding the position of the Head of the Archipelago Capital Authority. Therefore, through this research, we will answer issues related to the position of the Head of the Archipelago Capital Authority along with the logical consequences related to his role based on the regional government system. Normative legal research methods or what is usually called doctrinal legal research, the approaches used are the statutory approach and the conceptual approach. The research results show that the position of the Head of the Nusantara Capital Authority is as head of a special regional government at the provincial level. The logical consequences received from this regulation are that the election, appointment and dismissal are carried out directly by the President as per the President's prerogative, the regions are centralized, and there is no Regional People's Representative Council (DPRD) as an instrument of regional autonomy.